Reflexão sobre uma proposta avaliativa de um livro didático de curso livre sob a perspectiva da linguagem como prática social - Schneider, Luciane (Universidade do Vale do Rio dos Sinos, 2017)
Language teaching evolution in Brazil shows how additional language learning has lost and gained value in different moments of the history of the country. In this scenario, text books and their extra material packs became constantly present in the language teaching context and assumed a central role in the definition of free language courses curriculums, in teaching and learning methodologies and in language evaluation processes. In this context, perhaps as or even more important is the understanding of language that have the participants involved in the teaching-learning process of an additional language, since this understanding might define their beliefs about teaching and learning language, language use and evaluation of language use. The present study has then dedicated to analyze how a textbook evaluation pack is related or not to the conception of language use and language use evaluation as a social practice. So as to observe how close or how distant the material is from this understanding of language, a unit from Oxford’s Engage text book and its test pack were analyzed and confronted with the theories that understand language as a social practice. Adjustments and complements were then suggested with the intention to make the analyzed material closer to the understanding of language as a media to act and do things in the real world rather than a set of words and grammar rules. We believe the analysis; debates and results of the present study might contribute to a more reflexive teaching and evaluative practice in the area of additional language teaching and might be able to increase interest in new research in this area.
Keywords: Livro didático; Avaliação; Uso da linguagem; Avaliação da linguagem; Curso de idiomas; Línguas adicionais; Textbook; Evaluation; . Language use; Language evaluation; Free language course; Additional language